Enhancing participation and governance in water resources management - Jansky, Libor (ed.) (New Delhi, 2006)
Increasing demand for water has been identified as one of four major factors that will threaten human and ecological health over the next generation. As public health, development, economy and nature suffer; ensuring access to clean water is rising toward About The Author: Libor Jansky is Senior Academic Programme Officer in the Environment and Sustainable Development Programme at the United Nations University, Tokyo, Japan. Juha I. Uitto is Senior Evaluation Advisor at the United Nations Development Programme Evaluation
Keywords: Water resource management